An FPGA-Based System for Remote Data Monitoring of Underwater Gravity Measurement. Issue 2 (January 2021) - Liu, Yilin; Yu, Ruihang; Cao, Juliang
Abstract: Considering that underwater gravity measurement has the characteristics of a large amount of data and poor communication conditions, a data transmission link based on FPGA and wireless network is designed. The build of the wireless network could get rid of the dependence on cable and increase the adaptability to the working environment onboard. The multi-level wireless network is easy to expand and the compatibility and extension of equipment are better than the traditional wired transmission by cables, which enables devices to keep safe by working in the room rather than on the deck. In this condition, FPGA (Field Programmable Gate Array) can be used to preprocess the gravimeter data, and process the original miscellaneous data information into a short and effective data frame, which effectively reduces the communication pressure and makes the data transited by wireless network possible. The experiment shows that the design can effectively transmit the effective data collected by the deep-sea gravimeter and display the data in real-time on the remote computer when the mobile network bandwidth is about 1Mbps.